Cremian Congo Hemorrhagic Fever Outbreak Jabbi, Aug 2023 - Dr Zeba Nasir; Dr Muhammad Mudassar; Dr Nadia Noreen (International Journal of Infectious Diseases)
Introduction: In a public health rapid response to a confirmed case of Crimean-Congo Hemorrhagic Fever(CCHF) through ELISA/PCR involving a male cattle farmer, aged 51 and subsequent death of the patient was investigated to assess the situation, event based surveillance including contact tracing and raising Community awareness regarding the disease, signs and symptoms and preventive measures, vector surveillance and implementation of necessary preventive measures. Methods: Interviews were conducted with community members to identify potential contacts and assess their health status. Information regarding livestock, routine immunizations, disinsection measures along with frequency and animal handling practices was also collected. Detailed information about the deceased patient, including his medical history, symptoms, details of contacts after the start of symptoms, laboratory tests results, treatment record, healthcare facilities attended, contact tracing and the circumstances leading to his hospitalization with subsequent death. Risk factors were identified using questions related to travel and trade of cattle, hygiene practices, vector control measures, number of infected cattle and possible factors related to other hemorrhagic fevers. The team investigated the presence of ticks, which are known vectors for CCHF, in the local environment. Healthcare facility and laboratory testing and critical reporting practices were assessed for Triaging. Results: Potential contacts were identified with sampling and line listing for screening purposes to rule out secondary cases and outbreak propagation. Contacts were isolated for 14 days. No secondary cases were identified. Livestock department was also taken onboard for implementation of control measures to control the spread of the disease. Additionally, animal samples were collected for laboratory testing to identify any potential reservoirs of the virus but were reported negative. Discussions: Recommendations for improvement were provided in the form of triaging the patients, sensitization against severity of hemorrhagic fevers, spectrum of hemorrhagic fever, endemicity, critical laboratory results for urgent referral, notification to Focal points, infection control measures and isolation of suspected cases.Public awareness sessions were conducted to educate the local population about CCHF, its transmission, preventive measures and emergency measures to be taken in case of development of probable symptoms. Emphasis was placed on safe livestock handling and tick control. Conclusions: Necessary steps were taken to control the outbreak, educate the community, and prevent further transmission of the virus. Continuous monitoring and follow-up revealed no secondary cases. Strict actions involving animal and human health departments for efficient communication and early intervention were taken to ensure that the situation remains under control.Public health awareness is required to engage the general population, raise awareness, and develop policies to ensure disease surveillance.